Immunization Practices of Pediatricians for Children Younger Than Five Years in Coastal South India. (April 2015) - Mithra P., Prasanna; Unnikrishnan, B.; T., Rekha; Kumar, Nithin; Chatterjee, Pratik Kumar; Holla, Ramesh
Context: Immunization helps in controlling infectious diseases. Child immunization is an important component of child survival programs in India, which mainly follows the National Immunization Schedule. Also, many of the injection practices followed are not safe.Aims: To study the practices of pediatricians toward the immunization of children younger than 5 years and injection-related waste management.Settings and Design: Cross-sectional study carried out in the city of Mangalore, a rapidly developing city in southern India.Methods and Material: All the practicing pediatricians were included in the study and an interview was done on prior appointment using pretested interview schedule in March 2012, after obtaining clearance from the institutional ethics committee. Data were analyzed using the Statistical Package for Social Sciences version 11.5.Results: Among the 54 practicing pediatricians in Mangalore, 42 were included in this study after exclusion criteria were applied. Among them, 71.4% were following the National Immunization Schedule, 5% did not prefer to give combination vaccines, 17% reported vaccine failure at least once in their practice, and 85.7% motivated the parents for future doses. Distance to the clinic and affordability were the major reasons for loss of follow-up. Only 38.1% used auto-disabled syringes, 11.9% did not observe the children following the immunization, and 45.2% did not use color coding for disposal of injection-related wastes. Mechanical hub cutters were preferred by 41% of the respondents.Conclusion: The study showed the diversity in immunization practices. The National Immunization Schedule is the most commonly followed schedule. However, the safety of the injection practices was limited.